2012
DOI: 10.4049/jimmunol.1103474
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Regulate CD8+ T Cell Priming and Dendritic Cell Migration during Influenza A Infection by IFN-γ and Perforin-Dependent Mechanisms

Abstract: An effective immune response against influenza A infection depends on the generation of virus-specific T cells. NK cells are one of the first-line defenses against influenza A infection. We set out to delineate the role of NK cells in T cell immunity using a murine model of influenza A infection with A/PR/8/34. We show that early T cell recruitment mainly occurs in the posterior mediastinal lymph node (pMLN). Depletion of NK cells significantly impaired both dendritic cell (DC) and T cell recruitment into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 52 publications
2
94
1
Order By: Relevance
“…Moreover, NK-cells also play important roles in bridging the innate and adaptive responses to IAV. For example, it was demonstrated that NK-cells regulated CD8 + T-cell priming and dendritic cell (DC) migration during IAV infection via IFN-c-and perforin-dependent mechanisms (Ge et al, 2012;Paust et al, 2010). However, uncovering the major and complex role of NK-cells in IAV infection requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NK-cells also play important roles in bridging the innate and adaptive responses to IAV. For example, it was demonstrated that NK-cells regulated CD8 + T-cell priming and dendritic cell (DC) migration during IAV infection via IFN-c-and perforin-dependent mechanisms (Ge et al, 2012;Paust et al, 2010). However, uncovering the major and complex role of NK-cells in IAV infection requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…25 Glycolytic reserve level is dependent on NK cells' maximum glycolytic flux and glycolysis to respond to an energetic demand. However, glycolysis was lower in ME/CFS compared to healthy controls but did not reach statistical significance.…”
Section: Cd56mentioning
confidence: 99%
“…Furthermore, production of IL-22 by NK and NKT cells has an important role in the repair of epithelial damage caused by IAV (26,27). Meanwhile, NK cells play important roles in bridging the innate and adaptive immune responses to IAV (28). The major and complex roles of NK cells in IAV infection still require further in-depth investigations.…”
mentioning
confidence: 99%